A táj és a haza „petőfiesítése”: (Az Uti jegyzetek néhány mondatáról) - Milbacher, Róbert (Studia Litteraria, 2024)
This paper analyses Petőfi’s Travel Notes which documents his travels in Upper Hungary. It examines Petőfi’s work as a source of identity construction, focusing on the texts creating his own sense of being Hungarian. They show us that taking possession of the national landscape and past comes with the appropriation of some parts of the aristocratic identity.